The Effect of Medication Administration Associated Factors on Anxiety and Depression of Hospitalized Patients - Fatemeh, Dabaghzadeh (Asian Journal of Pharmaceutics (AJP), 2016)
Context: Hospital anxiety and depression can lead to higher length of stay in hospitals. Aims: The aim of this study was to evaluate the relationship between drug administration associated factors and anxiety and depression of hospitalized patients in infectious ward and also to evaluate the impacts of clinical pharmacist interventions on anxiety and depression of hospitalized patients in infectious ward through administering medications. Settings and Design: This study conducted in the infectious ward of Afzalipour Hospital affiliated to Kerman Medical University and had two parts. The first part was a cross-sectional study and the second part was a randomized clinical trial. Subjects and Methods: Patients on the 3rd or 4th day of hospitalization, who were between 16 and 85-year-old were included in this study. To measure anxiety and depression in patients, we used the Hospital Anxiety and Depression Scale. Statistical Analysis used: We used Spearman rank test, Mann–Whitney U-test, Kruskal–Wallis one-way analysis of variance, and Chi-square test. Results: In the first part, 156 patients participated. It was found that the number of medication and frequency of medication administration had a direct correlation with both anxiety and depression. In the second part, 104 patients enrolled. It was found that the presence of clinical pharmacist did not have any significant effect on anxiety, depression, frequency of medications administration, and the number of medications. Conclusions: It was concluded that drugs associated factors had a significant effect on anxiety and depression of hospitalized patients.